A historical, economic, and technical-scientific approach to the current crisis in the development of antibacterial drugs: Promising role of antibacterial peptides in this scenario. (June 2023) - Guevara, Yeimer A.S.; Santos, Maria H.C.; Gomes, Francisco I.R.; Sheheryar,; Mesquita, Felipe P.; Souza, Pedro F.N.
Abstract: The emergence of antibiotic resistance (AMR) is a global public health problem. According to estimates, drug-resistant bacteria infect 2 million patients and perish 23, 000 annually. To overcome this problem, antimicrobial peptides became a potential solution based on a new mechanism of action against bacteria. This article addresses the phenomenon of antibacterial resistance in most of its nuances, responding to historical, technical-scientific, and economic aspects. Likewise, it explores new therapeutic approaches to combat multi-resistant pathogens, specifically concerning antibacterial peptides, as a potential therapeutic tool to mitigate the current crisis of antibacterial drugs. It is expected that, with technological advances, especially with the advent and adoption of artificial intelligence, there will be an increase in diversified synthetic peptide production, which can face the challenges that we have in terms of antibacterial drugs. Highlights: Humanity is not prepared for coming resistant pathogens. Human action accelerated microbial resistance. Bacterial resistance is a serious threat to public health. Antimicrobial peptides are a potential solution to overcome microbial resistance. The unique mechanism of action of peptides makes it difficult the acquaintance of resistance.